Critical Issues of Chemical Kinetics in MILD Combustion - Sabia, Pino; de Joannon, Mara (Frontiers in Mechanical Engineering, 2020)
Mild combustion processes occur with mixtures highly diluted and pre-heated by a strong recirculation of hot exhausted gases (thus mass and sensible enthalpy) within the combustion chamber. This strategy configures a process based on auto-ignition kernels outside or close to flammability limits transported by convection in the combustion chamber, thus defining a process with unique physical and chemical features drastically different from traditional deflagrative-diffusive flames. The paper aims at analyzing the recent issues relative to kinetic aspects involved in MILD combustion processes. First, the paper comes through the identification of peculiar experimental features of simple hydrocarbons oxidation process induced by highly-preheated and diluted conditions in model reactors typical of chemical engineering. Second, the effects of steam and carbon dioxides on fuel oxidation process, whose presence within the combustion chamber is imposed by high levels of hot gas recirculation, are addressed. Third, the paper comes through a thorough analysis of recent scientific contributions on kinetic aspects of MILD combustion processes to identify the critical points in modeling activities.